Caracterização, classificação e as inter-relações entre os atributos do solo em agroecossistemas, Martins-RN - Farias, Phâmella Kalliny Pereira (2019)
As complex interactions between the various formation factors result in a natural variability of soil classes in the landscape. Thus, soil management that does not consider its limiting factors contributes to the degradation of soil resources, accelerating or impacting human activities on the environment. Thus, the present study aimed to characterize, classify and evaluate as interrelationships between soil resources in Sítio Poção agroecosystems, located in Martins / RN, using a multivariate analysis to distinguish formed environments in relation to specified attributes. A survey was carried out at Sítio Poção, located in Martins-RN, where nine representative soil records were opened for morphological description, collection of deformed and undeformed samples for chemical, statistical and chemical soil analysis, using pedological classification. , infiltration and water retention field trials. The soils were classified as: Neossolo Flúvico Ta Eutrófico típico (Aeric Fluvaquents); Cambissolo Háplico Ta Eutrófico típico (Aquic Haplustepts); Luvissolo Crômico Órtico típico (Rhodic Kanhaplustalfs); Planossolo Háplico Eutrófico típico (Rhodic Kanhaplustalfs); Neossolo Litólico Chernossólico típico (Lithic Udipsamments); Argissolo Vermelho-Amarelo Eutrófico típico (Typic Kanhaplustults) and Neossolo Litólico Eutrófico típico (Lithic Udipsamments). All horizontal described acid reaction and eutrophic character. The clay fraction and Al3+ are the most used attributes in the Argisols class distinction, while the silt fraction, K+, Na+, COT, CET and CTC, in the superficial horizontal, allows the differentiation of Neossolos Flúvicos. The position in the landscape, the minimum adopted crop and the addition of agricultural residues in the agroecosystems directly influence the most used attributes in the differentiation of the displayed soil classes, linked as physical characteristics (sand, silt and clay) and as chemical (nutrient availability). In agroecosystems, a basic infiltration velocity was high, being a vegetable area two (Neossolo Litólico Chernossólico típico) and presenting a greater accumulated infiltration. Total organic carbon, a silt fraction and a basic infiltration rate are the factors that most influence the distinction between the native forest area (Luvissolo Crômico Órtico típico) and the greenery area two (Neossolo Litólico Chernossólico típico). A clay clay, flocculation degree and aggregates is available in water and contributes to the differentiation of native forest area two (Argissolo Vermelho-Amarelo Eutrófico típico). In relation to the soil water characteristic curve, the Neossolos (profiles one, three, six and nine) reported similarity in water saturation and retention, except for the superficial layers in profiles one and three that obtained higher retention. The highest available water content occurred in the Argissolo Vermelho-Amarelo Eutrófico típico. A texture, like management practices, has a direct influence on the soil water retention and distribution process. The maintenance and increase of organic matter favor the retention of water in sandy soil soils such as Neossolos. Neossolos Flúvicos are the ones that most draw water from their surface surfaces, while the Argissolo Vermelho-Amarelo retain more water in the subofficial layers. The attributes selected for the basis of mass and volume, microporosity, total porosity, determined and aeration porosity, are the most identified in the distinction of environments formed in the study areas.